Pemanfaatan Buah Mengkudu (Morinda citrifolia L.) Sebagai Adsorben Untuk Meningkatkan Mutu Minyak Jelantah - Juliana, I Nengah; Gonggo, Siang Tandi; Said, Irwan (Jurnal Akademika Kimia, 2015)
The aim of this study is to lower the value quality parameters of used cooking oil to reach the national industry standards using adsorbent of noni (morinda citrifolia L.) fruit as well as to determine the optimum concentration (% w/w) of noni in increasing quality of used cooking oil. The parameters in this study are the water content, free fatty acids, colour and density. The method used to determine the water content and free fatty acid levels were the gravimetric method and acid-base titration, while determination of the colour and density used UV-Vis spectrophotometer and pycnometer. The concentration of noni adsorbent in the oil refining process varied ie 12%, 15%, 18%, 21%, and 24%. The results showed that the water content, free fatty acids, and the density decrease with an increase in adsorbent. The oil colourwas brighter with increasing noni fruit adsorbent used. The study showed that the noni fruit adsorbent can lower the value quality parameters of used cooking oil, and only the density from the four parameters did not meet ISO standard. The concentration weight per weight (% w/w) optimum noni fruit was 24%.